Imaging Beam‐Sensitive Materials by Electron Microscopy. Issue 16 (28th February 2020) - Chen, Qiaoli; Dwyer, Christian; Sheng, Guan; Zhu, Chongzhi; Li, Xiaonian; Zheng, Changlin; Zhu, Yihan
Abstract: Electron microscopy allows the extraction of multidimensional spatiotemporally correlated structural information of diverse materials down to atomic resolution, which is essential for figuring out their structure–property relationships. Unfortunately, the high‐energy electrons that carry this important information can cause damage by modulating the structures of the materials. This has become a significant problem concerning the recent boost in materials science applications of a wide range of beam‐sensitive materials, including metal–organic frameworks, covalent–organic frameworks, organic–inorganic hybrid materials, 2D materials, and zeolites. To this end, developing electron microscopy techniques that minimize the electron beam damage for the extraction of intrinsic structural information turns out to be a compelling but challenging need. This article provides a comprehensive review on the revolutionary strategies toward the electron microscopic imaging of beam‐sensitive materials and associated materials science discoveries, based on the principles of electron–matter interaction and mechanisms of electron beam damage. Finally, perspectives and future trends in this field are put forward. Abstract : Imaging beam‐sensitive materials by electron microscopy is of fundamental significance for materials science but remains a great challenge. A comprehensive review of the essential advances in electron microscopy techniques toward the dose‐efficient imaging of beam‐sensitive materials is provided. These advances have led to significant materials science discoveries through the elucidation of crystal and local structures.